Carpal tunnel syndrome : an analysis on the effect of hand tools in batik factory - Muhammad Lutfi Mohsein Bin Rozman (2023)
Musculoskeletal disorder is one of the Ergonomic problems which is because of Repetitive, force and Awkward Posture. The surgery and medication now is not sufficient to overcome this problem.